Pengaruh Kemampuan Metakognitif Terhadap Kemampuan Menyelesaikan Masalah Hukum Newton II Pada Mahasiwa Pendidikan Fisika FKIP Universitas Syiah Kuala - Andry, Mustaqim; Ngadimin, Ngadimin; Evendi, Evendi (Journal of Technology and Literacy in Education, 2022)
This study raises the issue of whether there is an impect of metacognitive ability on the problem solving skill in Newton’s second law of student in Physics Education Departement of Teacher Training Faculty and Education University of Syiah Kuala. This study aims to determine whether there is an The impect of metacognitive ability on the problem solving skill in Newton’s second law of student in Physics Education Departement of Teacher Training Faculty and Education University of Syiah Kuala. The research approach used is descriptive quantitative. The subjects in this study were 15 students of physics education class 2021 who were selected using the simple random sampling method. Data was collected using a questionnaire and essay test questions related to Newton’s second law material. Data analysis was carried out using SPSS. The results showed that there is a significant effect between impect of metacognitive ability on the problem solving skill in Newton’s second law of student in Physics Education Departement of Teacher Training Faculty and Education University of Syiah Kuala.